The Potential of Moxibustion and Rebozo Technique as An Alternative Solution for Pregnant Women with Breech Presentation - Sendy Firza Novilia Tono; Dianita Primihastuti; Devi Aprilia (GLOBAL HEALTH SCIENCE GROUP, 2025)
Breech presentation is a common malpresentation in pregnancy, associated with increased perinatal mortality and maternal morbidity. Conventional management such as cesarean section (CS) or vaginal breech delivery may cause trauma and risks for both mother and baby. Therefore, non-invasive complementary approaches, including moxibustion (Chinese traditional therapy) and rebozo (Mexican traditional technique), are being explored as safer alternatives. This study analyzed the potential of moxibustion and the rebozo technique in correcting breech presentation. A quasi-experimental design with a post-test only nonequivalent control group was used. Sixty pregnant women (28–36 weeks gestation) with breech presentation, participants were divided into intervention and control groups using purposive sampling. The intervention group received moxibustion at BL67 and rebozo for 10 consecutive days (10 minutes/day), while the control group performed knee-chest therapy with the same duration and frequency. Data on fetal position were collected through observation and analyzed using the Mann-Whitney test. Significant differences were found between groups (U = 0.00; Z = -6.145; p = 0.000), with the intervention group showing a higher rate of conversion from breech to cephalic presentation. Moxibustion and rebozo techniques are effective non-invasive alternatives for breech correction and may be integrated into antenatal midwifery education and care programs.